Permissive hypercapnia: what to remember. Issue 1 (February 2015) - Contreras, Maya; Masterson, Claire; Laffey, John G.
Abstract : Purpose of review: Hypercapnia is a central component of diverse respiratory disorders, while 'permissive hypercapnia' is frequently used in ventilatory strategies for patients with severe respiratory failure. This review will present data from recent studies relating to hypercapnia, focusing on issues that are of importance to anesthesiologists caring for the surgical and/or critically ill patient. Recent findings: Protective ventilatory strategies involving permissive hypercapnia are widely used in patients with severe respiratory failure, particularly in acute respiratory distress syndrome, status asthmaticus, chronic obstructive pulmonary disease and neonatal respiratory failure. The physiologic effects of hypercapnia are increasingly well understood, and important recent insights have emerged regarding the cellular and molecular mechanisms of action of hypercapnia and acidosis. Acute hypercapnic acidosis is protective in multiple models of nonseptic lung injury. These effects are mediated in part through inhibition of the NF-κB pathway. Hypercapnia-mediated NF-κB inhibition may also explain several deleterious effects, including delayed epithelial wound healing and decreased bacterial killing, which has been demonstrated to cause worse lung injury in prolonged untreated pneumonia models. Summary: The mechanisms of action of hypercapnia and acidosis continue to be elucidated, and this knowledge is central to determining the safety and therapeutic utility of hypercapnia in protective lung ventilatory strategies.